Information security and cryptology 6th International Conference, Inscrypt 2010, Shanghai, China, October 20-24, 2010 : Revised selected papers - Inscrypt (Conference) 2010 Shanghai, China); Lai, Xuejia; Yung, Moti.; Lin, Dongdai; SpringerLink (Online service). (Berlin London New York Springer, 2011)
This book constitutes the thoroughly refereed post-conference proceedings of the 6th International Conference on Information Security and Cryptology, Inscrypt 2010, held in Shanghai, China, in October 2010. The 35 revised full papers presented were carefully reviewed and selected from 125 submissions. The papers are organized in topical sections on encryption schemes, stream ciphers, sequences and elliptic curves, secure computing, hash functions, key management, digital signatures, privacy and algebraic cryptanalysis, hashing and authentication, and hardware and software issues.
Electronic reproduction.
Keywords: Computer security -- Congresses; Data encryption (Computer science) -- Congresses; Cryptography -- Congresses; Electronic books